Meeting Students' Basic Needs Through Free Nutritious Meals Program at School - Wiedya Listrina; Nora Saiva Jannana; Sedya Santosa; Tarwiyati; Aning Puspita Ningrum (JPP (Jurnal Pendidikan dan Pembelajaran), 2026)
Background: The effectiveness of school-based nutrition intervention programs in improving students’ readiness to learn continues to yield mixed results, particularly when implemented in educational settings with heterogeneous social characteristics.Objective: This study aims to analyze the fulfillment of students’ basic needs through the Free Nutritious Meal Program (MBG) and its implications for learning readiness and the learning climate at MTs Hidayatullah, Temanggung Regency, Central Java.Method: This study employs a qualitative approach with a case study design. Participants included eight students, four teachers who also served as homeroom teachers, the school principal, and the program coordinator, all selected through purposive sampling. Data were collected through observations in 10 classes (grades VII–IX), in-depth interviews, and documentation. Data analysis was conducted using the Miles, Huberman, and Saldaña interactive model through continuous data reduction, data presentation, and drawing of conclusions.Results: The results indicate that the MBG Program contributes to meeting students’ physiological needs by providing meals during school hours and reducing distractions caused by hunger. However, its impact on learning concentration, attendance, learning behavior, and emotional well-being has not yet shown significant and consistent changes.Conclusion: These findings suggest that meeting physiological needs is insufficient to enhance student engagement in learning without the support of psychosocial factors and a broader learning environment.